Biofilm Production by Uropathogens like Klebsiella spp and Pseudomonas spp and their Antibiotic Susceptibility - Mahato, Sanjay; Mandal, Pinki; Mahato, Ajay (Birat Journal of Health Sciences, 2020)
Introduction: Urinary Tract Infection (UTI) causes inflammation which is a common, painful and sometimes life-threatening condition as well. Despite high prevalence of bacteriuria, the information on biofilm forming bacteria is negligible.Objectives: This study aims at understanding the status of the biofilm forming nature of Klebsiella spp and Pseudomonas SPP and their drug resistance property with several class of antibiotics with a prime focus on resistance pattern against few penicillin based drugs to few empirical drugs in today's time.Methodology: Urine samples were analyzed and the isolates were biochemically identified. Then, the isolates were tested for several drugs so as to identify multidrug resistance nature of isolates by Kirby-Bauer Disc method. Biofilm forming nature was examined on Congo Red Agar.Results Out of 35 urine samples, 13 isolates (37.1%) were found to be positive with significant bacteriuria. Eight samples (22.8%) showed incidence of Klebsiella spp. and 5 samples (14.3%) showed P. aeruginosa. The prevalence of Klebsiella spp. (Klebsiella pneumoniae (46.2%) and K. oxytoca(15.4%)) and P. aeruginosa was found to be 61.4% and 38.6% respectively. 66.6% of K. pneumoniae and 50% K. oxytocawere biofilm forming pathogen.K. pneumoniae andK. oxytoca were resistant to amoxycillin, amoxycillin-clavulanate, and cefoxitin; while were sensitive to nitrofurantoin and azithromycin.P. aeruginosa were sensitive to azithromycin(100%), but showed 60% resistance to levofloxacin and ofloxacin. Eight (61.5%) isolates were found to be MDR. 100% of Klebsiella oxytoca (n=2), 66.7% of Klebsiella pneumoniae (n=4), and 40% of Pseudomonas aeruginosa (n=2)were multidrug resistant (MDR).Multiple antibiotic resistance (MAR) indices of bacteria revealed that all the 13 isolates were Multi-Antibiotics Resistance strains.Conclusion Biofilm forming nature is now much greater in Klebsiella spp; while most of the isolates like Klebsiella and Pseudomon as are multidrug resistant.